Manipulation with soft-fingertips for safe pHRI - Armendariz, Jorge; García-Rodríguez, Rodolfo; Machorro-Fernández, Felipe; Parra-Vega, Vicente (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
Manipulation with soft-fingertips is proposed as a tool for interacting with rigid objects, based on an online bilateral teleoperation fuzzy controller, without time delay. The fuzzy inference engine tunes continuously the force feedback gain to increase awareness of physical interaction so as to grasping is achieved. In contrast to the case of rigid fingertip, wherein infinitely small contact point is assumed, it is argued that our scheme allows safe and intuitive interaction, which has proved effective in an experimental study with 19 subjects. Results indicate success due to feedback of slave contact force to the human user. Subjects consistently judge comfort and easiness of manipulation, with an experimental two-hand prototype.